IMPLEMENTATION OF THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL IN INCREASING MOTIVATION AND LEARNING OUTCOMES OF GRADE VIII STUDENTS OF DAARUL QURAN COLOMADU JUNIOR HIGH SCHOOL ON PYTHAGOREAN THEOREM - Nur Harihadi (LPPM Universitas Bina Bangsa, 2024)
The low completeness of mathematics learning on the material of the Pythagorean theorem is wavered by the disinteractive interest of students in the process of learning activities. The purpose of this study was to obtain a description of the implementation of the Problem Based Learning model to improve the learning outcomes of grade VIII students of Daarul Quran Colomadu Junior High School on the Pythagorean Theorem material. This type of research is classroom action research that refers to Kemmis and Mc. Taggart's design, namely planning, implementing actions, observation and reflection. The study was conducted in two cycles. The subjects of this study were grade VIII students of Daarul Quran Colomadu totaling 40 students. Data collection techniques are obtained from data from teacher and student observations. This research was conducted in two cycles and each cycle was carried out in two meetings. The results showed that learning using the Problem Based Learning type cooperative learning model can improve student learning outcomes as shown by an increase in the number of students who completed in the first cycle by 31 students (70%) and the number of students incomplete by 9 people (30%). In the second cycle, the number of students who were declared complete increased by 37 students with a percentage of 90% and 3 students declared incomplete with a percentage of 10%.